Systemic Lupus Erythematosus and Deficiencies of Early Components of the Complement Classical Pathway - Macedo, Ana Catarina Lunz; Isaac, Lourdes (Frontiers in Immunology, 2016)
The complement system plays an important role in the innate and acquired immune response against pathogens. It consists of more than 30 proteins found in soluble form or attached to cell membranes. Most complement proteins circulate in inactive forms and can be sequentially activated by the Classical, Alternative or Lectin Pathways. Biological functions such as opsonization, removal of apoptotic cells, adjuvant function, activation of B lymphocytes, degranulation of mast cells and basophils, solubilization and clearance of immune complex and cell lysis are dependent on complement activation. Although the activation of the complement system is important to avoid infections, it also can contribute to the inflammatory response triggered by immune complex deposition in tissues in auto-immune diseases. Paradoxically, the deficiency of early complement proteins from the Classical Pathway is strongly associated with development of systemic lupus erythematous (SLE) - mainly C1q deficiency (93%) and C4 deficiency (75%). The aim of this review is to focus on the deficiencies of early components of the Classical Pathway (C1q, C1r, C1s, C4, C2) proteins in SLE patients.